Spatial turns - Fisher, Jaimey (Rodopi, 2010)
Preliminary material /Editors Spatial Turns – Acknowledgements /Editors Spatial Turns – Introduction /Jaimey Fisher and Barbara Mennel – Mapping Vision: Goethe, Cartography, and the Novel /Andrew Piper – Just How Naughty was Berlin? The Geography of Prostitution and Female Sexuality in Curt Moreck’s Erotic Travel Guide /Jill Suzanne Smith – Mapping a Human Geography: Spatiality in Uwe Johnson’s Mutmassungen über Jakob [Speculations about Jakob, 1959] /Jennifer Marston William – Historical Space: Daniel Kehlmann’s Die Vermessung der Welt [Measuring the World, 2005] /Katharina Gerstenberger – Gendered Urban Spaces: Cultural Mediations on the City in Eighteenth-Century German Women’s Writing /Diana Spokiene – The Roots of German Theater’s “Spatial Turn”: Gerhart Hauptmann’s Social-Spatial Dramas /Amy Strahler Holzapfel – Urban Mediations: The Theoretical Space of Siegfried Kracauer’s Ginster /Eric Jarosinski – Protesting the Globalized Metropolis: The Local as Counterspace in Recent Berlin Literature /Bastian Heinsohn – Transnational Cinema and the Ruins of Berlin and Havana: Die neue Kunst, Ruinen zu bauen [The New Art of Making Ruins, 2007] and Suite Habana (2003)1 /Jennifer Ruth Hosek – From the Desert to the City and Back: Nomads and the Spaces of Goethe’s West-östlicher Divan [West-Eastern Divan, 1819/1827] /Kamaal Haque – Not All Who Wander Are Lost: Alfred Döblin’s Reise in Polen [Journey to Poland, 1925] /June J. Hwang – The Feminine Topography of Zion: Mapping Gertrud Kolmar’s Poetic Imagination /Carola Daffner – Jewish Colonia as Heimat in the Pampas: Robert Schopflocher’s Explorations of Thirdspace in Argentina /Will Lehman – Rewriting Home and Migration: Spatiality in the Narratives of Emine Sevgi Özdamar /Silke Schade – Transcultural Space and Music: Fatih Akın’s Crossing the Bridge: The Sound of Istanbul (2005) /Barbara Kosta – The Cult of the Cold and the Gendered Body in Mountain Films /Ingeborg Majer-O’Sickey – Panoptic Paranoia and Phantasmagoria: Fritz Lang’s Nocturnal City /Steven Jacobs – Subjective Topographies: Berlin in Post-Wall Photography /Miriam Paeslack – Kreuzberg as Relational Place: Respatializing the “Ghetto” in Bettina Blümner’s Prinzessinnenbad [Pool of Princesses, 2007] /Jaimey Fisher – Digital Geographies: Berlin in the Ages of New Media /Todd Presner. The phrase “spatial turns” signals the growing importance of space as an analytical as well as representational category for culture. The volume addresses such emerging modes of inquiry by bringing together, for the first time, essays that engage with spatial turns, spatiality, and the theoretical implications of both in the context of German culture, history, and theory. Migrating from fields like geography, urban studies, and architecture, the new centrality of space has transformed social-science fields as diverse as sociology, philosophy, and psychology. In cultural studies, productive analyses of space increasingly cut across the studies of literature, film, popular culture, and the visual arts. Spatial Turns brings together essays that apply a spatial analysis to German literature and other media and engages with specifically German theorizations of space by such figures as Siegfried Kracauer and Walter Benjamin. The volume is organized in four sections: “Mapping Spaces” addresses cartography in all forms and in its intersection with culture; “Spaces of the Urban” takes up one of the key sites of spatial studies, the city; “Spaces of Encounter” considers how Germany has become a contact zone for multiple ethnicities; and “Visualized Spaces” concerns the theorization of space in film and new media studies
10.1163/9789042030022
Keywords: Aufsatzsammlung; German literature; Space in literature; Cartography in literature; Cities and towns in literature; Cities and towns in motion pictures; Civilization; Ethnic relations; Motion pictures; Motion pictures; German; Motion pictures; Setting and scenery; Place (Philosophy) in art; Place (Philosophy) in literature; Setting (Literature); Criticism; interpretation; etc